Guidelines for dietary management of menopausal women with simple obesity - Brończyk-Puzoń, Anna; Piecha, Dariusz; Nowak, Justyna; Koszowska, Aneta; Kulik-Kupka, Karolina; Dittfeld, Anna; Zubelewicz-Szkodzińska, Barbara (Menopause Review/Przegląd Menopauzalny, 2015)
The problem of obesity affects all age groups. It is also observed among menopausal women. Menopause is the time in a woman’s life when, as a consequence of hormonal changes occurring in the body, the risk of overweight and obesity increases significantly and, therefore, so does the risk of metabolic and cardiovascular diseases. Excess body weight in menopausal women may also be of social and psychological importance since the occurring symptoms may considerably decrease quality of life and sexual activity of these women. Reduction of body weight in obese menopausal women should play a vital role in treatment of this group of patients. Therefore, adequate management seems to be essential, and it should involve dietary, pharmacological and/or surgical treatment, depending on the patient’s needs. Following a rational weight loss plan provided by a dietician under medical supervision may contribute to improvement of the health condition and quality of life. It is recommended to observe the guidelines on dietary management described in this article by adjusting a diet plan individually. The following work constitutes a review of articles from 2004-2014 which are available in the PubMed medical knowledge base and the Polish Medical Bibliography (Polska Bibliografia Lekarska). For this purpose, the following controlled vocabulary has been used: menopausal woman, menopausal diet, menopausal weight gain, menopausal weight loss, dietary management in menopause.